Hydrogeology of the Lake Muir–Unicup Catchment, Western Australia: an ecologically important area experiencing hydrologic change - Smith, Margaret G (Curtin University, 2010)
Identified in the Western Australian Government’s 1996 Salinity Action Plan as an important natural diversity area at risk from changing hydrology, the Lake Muir– Unicup Natural Diversity Catchment is in need of urgent management to minimise impacts to lake hydrology and vegetation health. Many of the wetlands in the south of the catchment have been designated under the Ramsar Convention as Wetlands of International Importance. Other wetlands elsewhere in the catchment have been prioritised according to the Convention guidelines and are awaiting to be officially listed.In the 1980 to 1990s changing hydrology related to land clearing was considered to result in dry-land salinisation. Although low pH groundwater was noted during the groundwater monitoring between 1997 and 2001, the implications of groundwater acidification were not realised. Groundwater acidification cannot be taken in isolation, and it quickly became apparent that a viable management plan could not be formulated until the hydrogeology and geochemistry were better understood.The aquifers present today are the result of a landscape that evolved during and since Australia and Antarctica rifted apart. The separation of these two land masses has resulted in the formation and preservation of five regolith units that make up the three aquifers: the surficial; the sedimentary; and the fractured and/or weathered basement rock aquifers. The late Eocene topography was modelled using known depth to basement rock and reprocessed airborne magnetic data, enabling the lateral and verticals extent of the aquifers to be determined.The hydraulic head data within the mapped aquifers led to the identification of a closed groundwater basin in the south of the study area with groundwater TDS values up to three times seawater.Three distinct hydrochemical facies have been recognised and in keeping with the marine aerosol signature the majority of the groundwater is a Na–Cl type water. The fractured and/or weathered basement rock aquifer in the south of the study area contains a water where the major cations are Ca and Na and is referred to as a Ca– Na–Cl type water. Anthropogenic process have resulted in the a Na–Mg–SO[subscript]4 type water associated with draining a peat swamp with the aim of mining the peat.All three aquifers contain iron rich water, and pyrite has been identified in the sedimentary aquifer and fractured and/or weathered basement rock aquifer. Of the three aquifers the sedimentary aquifer is the most likely to contain groundwaters with pH up to 6.3 that have minimal buffering capacity.